1996
DOI: 10.1177/00220345960750060601
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Ability of Intra-oral and Extra-oral Fibroblasts to Stimulate Extracellular Matrix Reorganization in a Model of Wound Contraction

Abstract: Intra-oral wounds, like wounds in children, demonstrate privileged healing when compared with adult wounds at extra-oral sites. This study investigated whether this preferential healing is related to an increased ability of oral mucosal fibroblasts to reorganize extracellular matrix (ECM) when compared with their dermal counterparts. ECM reorganization was investigated by means of a fibroblast-populated collagen lattice (FPCL) system. The effect of donor age was also investigated in this system. Differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
85
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 33 publications
11
85
2
Order By: Relevance
“…Cultures of primary foreskin fibroblasts were established as described previously (Stephens et al, 1996) and maintained in DME medium supplemented with 2 mM L-glutamine, non-essential amino acids, antibiotics (100 U/ml penicillin, 100 µg/ml streptomycin, 0.25 µg/ml amphotericin B) and 10% FCS at 37°C in a 5% CO2 humidified atmosphere. Prior to seven population doubling levels (PDLs) cells were considered primary cells.…”
Section: Isolation and Culture Of Fibroblastsmentioning
confidence: 99%
“…Cultures of primary foreskin fibroblasts were established as described previously (Stephens et al, 1996) and maintained in DME medium supplemented with 2 mM L-glutamine, non-essential amino acids, antibiotics (100 U/ml penicillin, 100 µg/ml streptomycin, 0.25 µg/ml amphotericin B) and 10% FCS at 37°C in a 5% CO2 humidified atmosphere. Prior to seven population doubling levels (PDLs) cells were considered primary cells.…”
Section: Isolation and Culture Of Fibroblastsmentioning
confidence: 99%
“…However, wound healing in the oral mucosa is clinically distinguished from dermal healing in terms of both its rapidity and lack of notable scar formation. Previous in vitro work has demonstrated that oral mucosal fibroblasts show increased migration, experimental wound re-population, and ECM re-organization compared with dermal fibroblasts (35,36). Consequently in trying to understand fibrosis, we have used dermal and oral mucosal fibroblasts as models of scarring and nonscarring fibroblast phenotypes, to identify the processes that underlie scar-free healing.…”
mentioning
confidence: 99%
“…The inflammatory response in wounded oral mucosa is less intensive than in skin, 6 and the expression of cytokines is also low in oral wounds during the healing period. [7][8][9][10][11] Saliva contains a group of cytokines, 12,13 which may provide a unique oral environment suitable for wound healing. However, skin grafts transposed into the oral cavity maintain the skin wound healing phenotype, 14 indicating that constitutive oral cellular phenotypes, not the oral environment, may play the primary role in the oral wound healing.…”
mentioning
confidence: 99%